The relationship among emotional intelligence, critical thinking, and speaking ability of Iranian EFL learners - Hassan Soodman Afshar; Masoud Rahimi (Teaching English Language, 2014)
The present study aimed at investigating the relationship among critical thinking, emotional intelligence and speaking ability of Iranian EFL learners. To this end, 100 learners majoring in English at private language institutes in Sanandaj were selected as the participants of the study. The participants filled out the Bar-On (1997) emotional intelligence questionnaire, took the California Critical Thinking Skills Test (CCTST) Form B, and sat an interview, the results of which were checked by Language Oral Ability Assessment checklist adapted from IELTS Speaking Skill Test. The results of the multiple correlation analyses revealed emotional intelligence, followed by critical thinking, correlated significantly highly with learners’ speaking ability. The results also revealed all components of emotional intelligence significantly correlated with learners’ speaking ability. The results further showed there was a significant positive relationship between critical thinking and emotional intelligence. Further analyses revealed that almost half of the components of emotional intelligence correlated significantly highly with critical thinking. The results of multiple regression analyses indicated that emotional intelligence was the strongest predictor of speaking ability followed by critical thinking. The results further indicated that among the components of emotional intelligence, assertiveness, social responsibility, and reality testing significantly predicted learners’ speaking ability.The results also showed among the components of emotional intelligence, only assertiveness significantly predicted learners’ critical thinking. The findings imply that learners who are emotionally intelligent and are critical thinkers are more capable in speaking skill. The results as well as the implications of the study are discussed in more detail in the paper.